1997
DOI: 10.1051/lait:1997545
|View full text |Cite
|
Sign up to set email alerts
|

Influence de trois haplotypes des caséines αsl, β et Κ fréquents en race bovine Normande sur la composition du lait et l'aptitude à la fabrication fromagère

Abstract: * Correspondance et tirés à part. 626V Nuyts-Petit et al au cours de la coagulation par la présure. Les mêmes échantillons ont servi à la fabrication de fromages de type Saint-Paulin à partir de 6 kg de lait (une traite). La proportion de caséine K est plus forte dans la caséine des laits BBB et CA 2 B gue dans les laits BA 2 A. Il en résulte une réduction de la taille des micelles (-15 % entre les laits BA 2 A et CA 2B) et une amélioration de l'aptitude à la coagulation par la présure. En microfabrications fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
2
5
0
1
Order By: Relevance
“…The coefficient ascribed to KCN in equation (a), is also negative and has the higher value. This result agrees weil with the data already obtained on cow milk: KCN content of individual milks was reported to be inversely related to micelle size [12,17]. The coefficient relating to KCN, -20.4, seems valid for milks others than goat milk.…”
Section: Polynomial Regressionssupporting
confidence: 92%
See 1 more Smart Citation
“…The coefficient ascribed to KCN in equation (a), is also negative and has the higher value. This result agrees weil with the data already obtained on cow milk: KCN content of individual milks was reported to be inversely related to micelle size [12,17]. The coefficient relating to KCN, -20.4, seems valid for milks others than goat milk.…”
Section: Polynomial Regressionssupporting
confidence: 92%
“…Many investigations have been done on cow milk to determine the relation between micelle size and casein composition. KeN content was found to be in inverse relation to mean micelle size, in cow milks from various breeds [17] and in cow milks containing different KeN variants [12]. In addition, the KCN proportion in artificial micelles made from bovine caseins was found related to micelle size in the same way [23].…”
Section: Introductionmentioning
confidence: 99%
“…The smaller casein micelle diameter gives a denser and firmer casein network [89,108], which improves fat retention in the coagulum. Such was the case with the association of variant B of β and κ-casein in the Normande cattle breed [35,91] or with the variant A of α s1 -casein, compared with defective variants, in goats [107] or with the variant C of α s1 -casein in sheeps' milk [101]. The example of variant C of β-casein in the Tarentaise cattle breed is a good illustration of the mechanisms that can be at the origin of the texture differences noted.…”
Section: Proteins and Fat Modificationsmentioning
confidence: 93%
“…During experimental microfabrications of washed-curd cheeses (Saint-Paulintype) using individual milk samples selected on the basis of genotype, filiation and lactation stage as well as chemical composition (identical fat/protein ratio), associating variants B of κ and β-caseins resulted in a much greater increase in cheese yield than could be achieved with each variant taken separately. The BBB curd microstructure was tighter than that of curds BA 2 A and CA 2 B, primary proteolysis was more extended for the BA 2 A cheeses (P < 0.01) and after ripening, the BBB cheeses were firmer, less elastic and more brittle than the other ones [90,91]. In another study, 42 Holstein, Montbéliarde and Tarentaise cows were distributed into two groups according to the genetic variants of β and κ-caseins.…”
Section: Effect Of Genetic Variantsmentioning
confidence: 99%
“…Within the CSN3 locus, for CSN1S1 variant BB and CSN2 variant A 2 A 2 , BB-A 2 A 2 -AA milk showed the worst MCP values (P < 0.05). The best coagulation characteristics of CSN3 BB milk compared with CSN3 AA milk were demonstrated by Nuyts-Petit et al (1997) in Normande cows and by Walsh et al (1998a) in Irish Holstein cows; this was due to the lower loss of casein and fat of CSN3 BB milk during cheesemaking (Hartung and Gernand, 1997;Pabst, 1998;Walsh et al, 1998b). Mariani and Summer (1999) and Mariani et al (2002) also reported that CSN3 BB milk is characterized by a higher CSN3 content and by smaller casein micelles.…”
Section: Milk Clotting Propertiesmentioning
confidence: 99%